2005
DOI: 10.1158/0008-5472.can-05-1160
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced Phosphorylation of Chk2 in an Ataxia Telangiectasia Mutated–Dependent Manner

Abstract: Chk2 is a serine/threonine kinase that signals to cell cycle arrest, DNA repair, and apoptotic pathways following DNA damage. It is activated by phosphorylation in response to ionizing radiation, UV light, stalled replication forks, and other types of DNA damage. Hypoxia is a common feature of solid tumors and has been shown to affect the regulation of many genes, including several DNA repair factors. We show here that Chk2 is phosphorylated on Thr68 and thereby activated in cells in response to hypoxia, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 33 publications
5
69
0
Order By: Relevance
“…It is also likely that, like Chk2, Chk1 contributes to the reoxygenation-induced cell cycle arrest. 30,45 Taken together these data indicate that Chk1 functions during both hypoxia and reoxygenation. We have carried out a modified form of our colony survival experiment to determine in which phase, hypoxia or reoxygenation, the cells are more sensitive (Fig.…”
Section: Chk1 Signalling In Hypoxia/reoxygenationmentioning
confidence: 61%
“…It is also likely that, like Chk2, Chk1 contributes to the reoxygenation-induced cell cycle arrest. 30,45 Taken together these data indicate that Chk1 functions during both hypoxia and reoxygenation. We have carried out a modified form of our colony survival experiment to determine in which phase, hypoxia or reoxygenation, the cells are more sensitive (Fig.…”
Section: Chk1 Signalling In Hypoxia/reoxygenationmentioning
confidence: 61%
“…Anoxia can induce an ATM-and ATR-mediated G 1 and intra-S (DNA replicative) arrest and a further G 2 phase arrest upon reoxygenation (42)(43)(44). This could lead to altered S and G 2 fractions that may bias HR protein expression and function, given that HR is cell cycle dependent (37).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the ATM and ATR kinases are activated under severe hypoxia or anoxia (,0.1% O 2 ) (Bencokova et al, 2009;Freiberg et al, 2006;Gibson et al, 2005;Hammond et al, 2004). This could bias the use of c-H2AX as a biomarker of exogenous DNA-dsbs under hypoxic conditions, given its dependence on ATM.…”
Section: G0-g1 Synchronized Fibroblasts Represent a Robust Model To Smentioning
confidence: 99%